Robotic Excision of a Huge Seminal Vesicle Cyst, Including Intracystic Papillary Adenoma, Saving Fertility - Tae Hoon Oh; Ill Young Seo (Urogenital Tract Infection)
A seminal vesicle cyst is a rare disease, and an intracystic papillary adenoma within the seminal vesicle is extremely rare. The diagnosis and treatment of these diseases are challenging because of the limited data. This paper presents a robotic excision of a huge seminal vesicle cyst, including an intracystic papillary adenoma, preserving fertility in a 40-year-old man.